Cardiovascular diseases and diabetes mellitus - Yavuz, Senol; As, Ahmet Kağan; Engin, Mesut; Koca, Nizamettin; Cander, Soner (The European Research Journal, 2022)
Cardiovascular diseases are among the leading causes of death worldwide. Atherosclerotic cardiovascular diseases consist of a broad spectrum of diseases such as coronary artery disease, carotid artery disease, peripheral artery diseases, cerebral vascular diseases and visceral artery diseases. Although atherosclerosis occurs over time due to age; hypertension, hyperlipidemia, smoking, and diabetes mellitus are important factors that play a role in the emergence of atherosclerosis. Diabetes mellitus has an active role in the development of atherosclerotic cardiovascular disease. It is expected that there will be a significant increase in the incidence of diabetes-related cardiovascular diseases in the future. In this review, it is aimed to review the coexistence of diabetes with different cardiovascular diseases and its menanisms.